Towards the expediency and leniency of Islamic finance through Islamic micro credit financing - Ariffin, Muhammad Irwan (Jabatan Ekonomi Awam & Kewangan, Fakulti Ekonomi, Universiti Utara Malaysia, 2005)
This paper is intended to study the opportunities available for Islamic banks to explore the micro credit financing in Malaysia. The effectiveness of micro credit financing, as a tool to eradicate poverty, is factual since many countries that practice the scheme are able to provide the poor with income-generating jobs. In Malaysia, despite the rapid development in the banking sector, little progress is seen in Islamic micro credit financing. Islamic micro credit financing is an effective tool to link between Islamic banks and the poor. This will enhance the moral features that have been lacking in Islamic banking and finance all these years. The lack of research and development in the Islamic banking and financial products; together with high transaction costs, moral hazard and deficient securities with small units contributed to the unwillingness of Islamic banks to explore micro credit financing area. Al-Mudharabah and al-musharkaah contracts are the most suitable mode to be used in Islamic micro credit financing since the interest of both parties are protected. The Islamic banks need to optimize their resources toward helping the poor to gain profit in their business, and they are given greater role in the economy since they have to ensure the capital usage must fulfill the economic objectives of syari'ah: profitable as well as halal.